Autoregressive integrated moving average (ARIMA) implementation in number of visitors forecasting at the Balai Layanan Perpustakaan DPAD DIY - Ndaru Ramadhan; Selvi Centia; Jovanscha Qisty Adinda Fildzah Arifianto; Nurul Asiah (AXIOM : Jurnal Pendidikan dan Matematika, 2025)
Government organizations must provide excellent services to their citizens. The Balai Layanan Perpustakaan DPAD DIY, one of the government organizations for library affairs, must also provide the best library services. One way is to forecast the number of visitors to prepare better services for the future. This research aims to predict the number of visitors in 2024. This research used historical data in the form of the number of visitors at the Balai Layanan Perpustakaan DPAD DIY in 2023. This data was analyzed using the ARIMA Model (2,0,6) with the results that this model had a MAPE value of 25.35%, so it was accurate enough to be used in forecasting. Based on forecasting results, it is known that the total number of visitors to the Balai Layanan Perpustakaan DPAD DIY in 2024 will be 115,213. The fewest visitors were in January 2024, as many as 5,198 visitors, while the most were in June 2024, as many as 13,605 visitors.